Transmedia’s Implications of the use of RPG and Wargame as tools to support Vast Narratives of Medieval Fantasy - Andrade, Leonardo; Dos Santos, Tiago; Gonçalves, Diogo Augusto; Antonio, Layla Stassun (Revista GEMInIS, 2011)
Emerging in the 1970s, the Wargame Chainmail and the first RPG shared the medieval fantasy genre to explore interactive narratives. In this article, we’ll analyze the main vast narratives of the medieval fantasy genre involving RPG and Wargames and its transmedia’s implications. Some systems of rules have their game mechanics discussed, building the basis for the experience of using the RPG as a tool for creative support and cohesion of narrative in the scenario Shiang’s Lands. Using rules of both, RPG and Wargame, this article exposes the creative process and the transmedia’s implications of the expe-rience analyzed.